When the Renal (Function) Begins to Fall: A Mini-Review of Acute Kidney Injury Related to Acute Respiratory Distress Syndrome in Critically Ill Patients - Marchiset, Antoine; Jamme, Matthieu (Frontiers in Nephrology, 2022)
Acute kidney injury (AKI) is one of the most frequent causes of organ failure encountered in patients in the intensive care unit (ICU). Because of its predisposition to occur in the most critically ill patients, it is not surprising to observe a high frequency of AKI in patients with acute respiratory distress syndrome (ARDS). However, few studies have been carried out to assess the epidemiology of AKI in subgroups of ARDS patients using recommended KDIGO criteria. Moreover, the mechanisms involved in the physio-pathogenesis of AKI are still poorly understood, in particular the impact of mechanical ventilation on the kidneys. We carried out a review of the literature, focusing on the epidemiology and physiopathology of AKI in patients with ARDS admitted to the ICU. We addressed the importance of clinical management, focusing on mechanical ventilation for improving outcomes, on AKI. Finally, we also propose candidate treatment strategies and management perspectives. Our literature search showed that AKI is particularly common in ICU patients with ARDS. In association with the classic risk factors for AKI, such as comorbidities and iatrogeny, changes in mechanical ventilation parameters, which have been exclusively evaluated for their outcomes on respiratory function and death, must be considered carefully in terms of their impact on the short-term renal prognosis.